Preventing Colorectal Cancer: A Detailed Guide to Screening Methods and Accessing Screening in Florida: FCS3399/FY1542, 7/2024 - Vilaro, Melissa J.; Westring, Valeria; Woodard, Jennifer; Purvis, Samara; Massey, LaTrina; Wood, Wendy (EDIS, 2024)
This is the second installment in the colorectal cancer prevention series. This article is intended for adults who fall within the recommended age range (45 to 75 years old) for colorectal cancer screening. This article aims to provide up-to-date information about several approved options available for colorectal cancer screening. Written by Melissa J. Vilaro, Valeria Westring, Jennifer Woodard, Samara Purvis, LaTrina Massey, and Wendy Wood, and published by the UF/IFAS Department of Family, Youth and Community Sciences, July 2024.